Burnout syndrome: the impact on people management and prevention ways - de Souza , Igor Siqueira; Nogueira, Kétylla Oliveira; Novaes, Adriana Esteves Gama; Sampaio, Rinaldo Jefferson (Seven Editora, 2023)
This scientific article discusses Burnout Syndrome: the impact on people management and ways of prevention. This study methodology will be anchored in two scientific axes: quantitative and bibliographic research. A field survey was carried out with 89 students from a private educational institution in the extreme south of Bahia through a closed questionnaire. The main results obtained in the sample were the presence of many symptoms that occurred in the three main dimensions approached by Benevides-Pereira (2002). This research’s current theme must be observed accurately by the people management because it is a silent and devastating danger to lives and it represents a warning factor for enterprises around the modern world. DOI: https://doi.org/10.56238/devopinterscie-001